Slope stability analysis of a landfill subjected to leachate recirculation and aeration considering bio-hydro coupled processes - Shi-Jin Feng (SpringerOpen, 2021)
Abstract During the operation of landfills, leachate recirculation and aeration are widely applied to accelerate the waste stabilization process. However, these strategies may induce high pore pressures in waste, thereby affecting the stability of the landfill slope. Therefore, a three-dimensional numerical analysis for landfill slope stability during leachate recirculation and aeration is performed in this study using strength reduction method. The bio-hydro coupled processes of waste are simulated by a previously reported landfill coupled model programmed on the open-source platform OpenFOAM and then incorporated into the slope stability analysis. The results show that both increasing the injection pressure for leachate recirculation and maximum anaerobic biodegradation rate will reduce the factor of safety (FS) of the landfill slope maximally by 0.32 and 0.62, respectively, due to increased pore pressures. The ignorance of both waste biodegradation and gas flow will overestimate the slope stability of an anaerobic bioreactor landfill by about 20–50%, especially when the landfilled waste is easily degradable. The FS value of an aerobic bioreactor landfill slope will show a significant reduction (maximally by 53% in this study) when the aeration pressure exceeds a critical value and this value is termed as the safe aeration pressure. This study then proposes a relationship between the safe aeration pressure and the location of the air injection screen (i.e., the horizontal distance between the top of the injection screen and the slope surface) to avoid landfill slope failure during aeration. The findings of this study can provide insights for engineers to have a better understanding of the slope stability of a bioreactor landfill and to design and control the leachate recirculation and aeration systems in landfills.